Heterogeneous time preferences and interest rates: The preferred habitat theory revisited - Frank Riedel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
The influence of heterogeneous time preferences on the term structure is investigated. Motivated by the Preferred Habitat Theory of Modigliani and Sutch, a model for intertemporal preferences accounting for preferred habitats is proposed. In a heterogeneous world, preferred habitats can explain humps in the yield curve. Agents with a long habitat prefer long term bonds to shorter instruments as the Preferred Habitat Theory predicts.
urn:nbn:de:kobv:11-10056153
Keywords: 330